Structural and functional characteristics of zooplankton communities in thermokarst lakes of Samoylov Island (Lena River delta, Republic of Sakha (Yakutia)) - L.A. Frolova; G.R. Nigamatzyanova (Учёные записки Казанского университета: Серия Естественные науки)
The structural and functional characteristics of zooplankton communities of two thermokarst lakes on Samoylov Island (Lena River delta, Yakutia) have been studied. A total of 76 taxa of hydrobionts have been found in the zooplankton community of the studied lakes. The taxonomic lists of the spring-summer zooplankton compositions have been provided. The complex of species determining the community structure has been defined. Rotifers determined the species diversity and zooplankton abundance in the lakes. The biomass values were defined by large copepods. Cold-water-dwelling northern species made the greatest contribution to the quantitative indicators of zooplankton. The seasonal dynamics of quantitative indicators of zooplankton has been analyzed. The current state of the lakes has been assessed using the saprobity index and species diversity.